Supporting Decision System for Recruitment of New Employees in the Department of Communication and Information of Dharmasraya District Using the AHP Method: Sistem Pendukung Keputusan Penerimaan Karyawan Dinas Komunikasi dan Informasi Kabupaten Dharmasraya d engan Metode AHP - Iis Gusmawati; Efri Yandani; Yusran Yusran (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2020)
The purpose of this study is the application of the AHP method in building a decision support system for hiring new employees to help the selection process of the Department of Communication and Information of the Dharmasraya Regency so that the process is more selective and in accordance with the expected criteria. This research conducted a variety of problems, such as: the needs of prospective employee criteria, selectivity of prospective employees, prospective employee data collection, the ability of prospective employees, and the needs of superior HR, Decision Support System (SPK) is a system that can help in making decisions by using computers / PC in making a decision. With the existence of a decision support system, it is expected to be able to assist in making the decision to recruit new employees appropriately. In the case of the recruitment of new employees at the Dharmasraya District DISKOMINFO, the Analytic Hierarchy Process (AHP) method is used to apply it to the decision support system in decision making. AHP Is a method for solving an unstructured complex situation into several components in a hierarchical arrangement, by giving a subjective value about the relative importance of each variable, and determining which variable has the highest priority affecting the outcome of the situation. This system is expected to be a very useful tool for optimal recruitment of prospective new employees.